A review on security challenges of wireless communications in disaster emergency response and crisis management situations. (15th January 2019) - Seba, Abderazek; Nouali-Taboudjemat, Nadia; Badache, Nadjib; Seba, Hamida
Abstract: In all disaster management mission areas such as prevention, protection, mitigation, response and recovery, the first pressing need is to establish a communication network for data collection, and especially for reliable real-time information exchange between emergency actors. Generally, when a crisis happens all the pre-existing communication networks are down and the different responders have heterogeneous equipment. Because of the hurry of the situation, a rapid deployment of a reliable, easily configurable, robust, inter-operable, low cost and secure network is needed. Wireless networks provide a promising communication infrastructure to all the situation tiers such as headquarter and rescue operators. The security considerations are vital due to the sensitive and real-time need for information exchange, in the spatial context of chaotic emergency and crisis situations. Numerous security threats can be found in the different wireless based communication architectures proposed for crisis management. In this paper, we study disaster management security needs and we present an overview of the communication architecture proposed for emergency situations. We also provide a security analysis of theses architectures and open issues to be tackled. Graphical abstract: